Comparison of Emodemo and Leaflet Nutrition Education on Knowledge and Attitudes of Mothers of Wasting Toddlers - Catur Wulandari; Zainiyah Rozi (Jurnal Ilmiah Kesehatan, 2026)
Wasting is a growth disorder characterized by a mismatch between a child's weight and height or length. The causes of wasting are divided into direct and indirect factors, with knowledge and attitudes considered indirect factors. This study aimed to analyze differences in knowledge and attitudes after education using emodemo and leaflet media among mothers of children aged 6–24 months with wasting in the working area of Banjar Health Center, Galis District, Bangkalan. This study employed a quasi-experimental design. The research instruments included a post-test questionnaire consisting of multiple-choice questions to measure knowledge and a likert scale form to assess attitudes. Data were analyzed using the Mann-Whitney test. The results showed a significant difference in mothers’ knowledge after education using emodemo media (p-value = 0.002). However, no significant difference was found in mothers’ attitudes after education using leaflet media (p-value = 0.062). In conclusion, there was a significant difference in the knowledge of mothers of children with wasting after receiving education through emodemo and leaflet media (p < 0.05). However, there was no significant difference in attitudes after the intervention (p > 0.05). Future research is recommended to not only measure knowledge and attitudes immediately after education but also conduct follow-up measurements several weeks or months later to assess retention and behavioral changes over time.